Lithium-based vs. Vanadium Redox Flow Batteries – A Comparison for Home Storage Systems. (November 2016) - Uhrig, Martin; Koenig, Sebastian; Suriyah, Michael R.; Leibfried, Thomas
Abstract: Since May 2013, more than 35, 000 home storage systems have been installed in Germany. Due to superior performance and significant price degression, lithium ion batteries (LiBs) are the dominating technology in this market. However, in 2015, a new technology became available for this application. Several manufacturers are now offering flow batteries in the required scale. This technology has low variable costs (€/kWh) and uses a wider SoC range. On the other hand, efficiency is lower than for the LiB and fixed costs (€/kW) are rather high. In this work, we examine how those properties influence the cost effectiveness for the use case of home storage. Therefore, we compare the performance of LiBs and vanadium redox flow batteries (VRFBs) using a household simulation framework. A unique approach of combining a sophisticated multi-physical flow battery model to obtain efficiency and operational limits with an advanced method of evaluating the economic contribution of a PV home storage system is applied. The benefit of increased self-consumption by a battery system is determined over a period of 20 years using a temporal resolution of 15 minutes. Simulated households are characterized by their individual annual energy demand (1, 000 to 10, 000 kWh/a) and annual energy generation by rooftop PV plants (500 to 15, 000 kWh/a). The study shows, that under the given assumptions, home storage for individual households is not an economically viable use case for any of the evaluated battery technologies. It has been found, that the batteries are not in operation and completely discharged for the better part of the year. This demonstrates the large potential for additional use cases, especially during winter time. In addition, it is shown that LiBs outperform VRFBs for every studied household. The efficiency gap between the two technologies is too large to become compensated by the larger useable SoC range. However, in terms of cost, especially for larger capacities, the VRFB can be competitive compared to the LiB. Therefore, further efforts should be undertaken to improve VRFB performance.